Quality Improvement Project to Improve Screening for Tobacco Use in Adolescent Inpatients at a Children's Hospital - Lauren A. Wagner; Adolfo L. Molina; Karisa Grizzle; Meghan E. Hofto; Lauren B. Nassetta; Mary M. Orr; Nichole Samuy; Erinn O. Schmit; Cassi Smola; Kathleen F. Harrington; Susan C. Walley (MDPI AG, 2019)
Tobacco use begins in adolescence for the majority of smokers. The purpose of this study was to increase screening and reporting of tobacco use in hospitalized adolescents at a tertiary care children’s hospital. We completed a nursing focus group to understand challenges and completed four iterative Plan-Do-Study-Act cycles, which included: (1) in-person nursing education regarding tobacco use screening, (2) addition of an e-cigarette-specific screening question, (3) the creation and dissemination of an educational video for nursing, and (4) adding the video as a mandatory component of nursing orientation. Run charts of the percentage of patients screened who reported tobacco use were created. Absolute counts of tobacco products used were also captured. From January 2016 to September 2018, 12,999 patients ≥13 years of age were admitted to the hospital. At baseline, 90.1% of patients were screened and 4.8% reported tobacco use. While the absolute number of adolescents reporting e-cigarette use increased from zero patients per month at baseline to five, the percentage of patients screened and reporting tobacco use was unchanged; the majority of e-cigarette users reported use of other tobacco products. This study demonstrates that adding e-cigarettes to screening increases reporting and suggests systems level changes are needed to improve tobacco use reporting.